Practice of pharmaceutical services and prescription analysis in internet-based psychiatric hospitals during COVID-19 pandemic in Wuxi, China - Du, Zhiqiang; Jiang, Ying; Lu, Rongrong; Zhou, Qin; Pan, Yiting; Shen, Yuan; Zhu, Haohao (Frontiers in Psychiatry, 2023)
Objective: To study the practice of pharmaceutical services in internet-based psychiatric hospitals, and to analyze the prescriptions to ensure the safety and efficacy of internet-based medication in Wuxi, China.Methods: All 1,259 internet-based prescriptions from our hospital in 2022 were collected, and data on patients' age, gender, diagnosis, medicationdrugs used, medicationdrug types, dosage forms, rationality of medicationdrug use, and reasons for irrationality were analyzed through descriptive statistics.Results: In the electronic prescriptions of internet-based psychiatric hospitals, females accounted for the majority (64.50%), with a female-to-male ratio of 1.82:1. Middle-aged and young adults accounted for the majority of patients (57.50%). There were 47 diagnosed diseases involved, with 89 types of medicationdrugs used and 1,938 drug prescriptions issued. Among them, there were 78 types of western medicine with 1,876 prescriptions (96.80%), and 11 types of traditional Chinese medicine with 62 prescriptions (3.20%). The main medicationdrugs used were anti-anxiety and antidepressant medicationdrugs (44.94%) and psychiatric medicationdrugs (42.21%). The dosage forms were all oral, with tablets (78.53%), capsules (17.54%), and solution preparations (2.17%) being the top three in frequency. According to the prescription review results, the initial pass rate of internet-based system review was 64.26%. After intervention by the internet-based system and manual review by pharmacist reviewers, the final pass rate of internet-based prescriptions reached 99.76%.The practice of pharmaceutical services and prescription analysis in internet-based psychiatric hospitals could significantly improve medication rationality, which fills the research gap in this field. In addition, it promotes the transformation of pharmaceutical service models.